The potential of natural conditions in juxtaposition with land consolidation – case study of Lubelskie voivodship (Lublin Region) - Małgorzata Dudzińska; Barbara Prus (Acta Scientiarum Polonorum. Formatio Circumiectus)
In Poland, land consolidation works are mainly carried out in the southern part of the country. In three administrative regions (voivodships): Lubelskie, Podkarpackie and Małopolskie, in the years 2004–2013, a large number of land consolidation projects were carried out compared to the national average, namely, above 20 thousand hectares in each of the regions. In other three regions (Warmińsko-Mazurskie, Zachodniopomorskie, Kujawsko-Pomorskie) there have been no land consolidation projects, although research shows (Jędrejek et al., 2014) that the need for consolidation works is found in all regions. According to Woch and Głażewski (2014), one of the reasons for this is the difficulty in the implementation of land consolidation projects resulting from the need to preserve the valuable natural qualities of the environment in protected areas. The aim of the article is to analyse and assess the natural potential of individual municipalities, as well as to juxtapose the calculated indices against the area size of the already completed land consolidation works. In the article, we attempt to answer the following questions: Is there a relationship between the natural conditions of the municipalities where the consolidation work on agricultural land was carried out, and the area size of the implemented consolidation projects in the studied area? Is the impact of the natural potential of municipalities positive or negative in relation to the on-going land consolidation projects? What are the environmental conditions of the municipalities in which the consolidation of agricultural land was carried out? The study involved the query of literature on the subject. Analysis and evaluation of natural conditions was made on the basis of research following a spatial-statistical approach. The potential of the natural environment has been analysed in terms of valorisation of the agricultural production space, analysis of the forest cover (afforestation) index, and the index of protected areas. A synthetic assessment of the natural environment potential index was made, and then Pearson’s correlation coefficient was calculated between the calculated environmental potential index, and the area size of the completed consolidation projects. The research area comprised the Lublin region (Lubelskie voividship). Administrative unit of the municipality served as the primary entity under assessment. The units in which land consolidation projects were carried out in the years 2004-2013 were analysed in detail. Research has shown that the potential of the natural environment in the majority of municipalities in the Lublin region has been determined on the medium level. It has also been shown that there is correlation dependence between the area size of the completed land consolidation projects and the level of the potential of natural conditions. The quality of the natural environment in rural areas is potentially threatened by the intensification of agricultural production, because economic expansion may affect the disappearance of natural habitats and reduce biodiversity. Therefore, preservation of natural potential is antagonistic to simultaneous actions aimed at improving the conditions of agricultural production. On the other hand, the threat to forms of nature protection comes from the lack of modernization of infrastructure in rural areas, including sewage and waste management, which are inseparable activities in the implementation of the land management and agricultural works.